(untitled) (Journal of the College of Basic Education, 2024)
The study aimed to prepare physical-cognitive exercises on some bio-kinematic variables and the accuracy of the jump serve skill (FLOAT) in volleyball, as identifying the effect of the researched exercises on the variables under study in volleyball, and the research community was represented by the players of Suleikh Sports Club for the 2023/2024 season and it was The research population was determined by a deliberate method to conduct the research on them. As for the research sample, it was chosen by random lottery method, provided that they met the requirements of the research, including the inability to reach the required level of accuracy in performing the skills well, as this was determined through observation and questioning the trainer, and their number reached (14). ) players aged (14-16) years, and the experimental group was chosen by random drawing and consisted of (6) players. (6) players were for the control group, and (3) players were chosen for the exploratory experiment from outside the research sample, and two players were excluded because they are libero players and are not permitted to perform offensive skills for the pre-test, and thus the percentage of the research sample reached (42.85%). The conclusions were: that the exercises prepared by the researchers had a positive impact in developing the biomechanical and skill variables for the accuracy of the wavy serve when jumping with a volleyball, which were calculated through kinematic analysis. The proposed exercises developed the level of skill performance for the skill of the wavy serve when jumping with a volleyball. The researcher recommends the use of modern devices for movement measurement and analysis by coaches to know the strengths and weaknesses when performing skills in general and the serving skill in particular for players who are late in learning skills.